2004
DOI: 10.1016/j.fsi.2003.08.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of cadmium and mercury on Pacific oyster, Crassostrea gigas (Thunberg), haemocytes

Abstract: In the past decades, shellfish culture has developed in a significant way around the world. However, culture areas are often subject to recurring anthropic pollution. The recrudescent presence of industrial wastes is a source of heavy metals and results in pollutant transfer towards the aquatic environment in estuarine areas. Because of their mode of life, bivalves, including mussels and oysters, are suggested as ideal indicator organisms. The development of techniques allowing the analysis of the effects of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(96 citation statements)
references
References 51 publications
6
88
0
2
Order By: Relevance
“…Copper is one of the agents involved in the oxidative stress [2,24] by the formation of ROS [25,26]; the exposure of marine mollusks to this metal induces lipid peroxidation [27]. Against these hazards, mussels, particularly the species Perna perna and Mytilus galloprovincialis, have developed enzymatic antioxidant defense mechanisms such as super oxide dismutase (SOD, EC 1.15.1.1) or CAT (EC 1.11.1.6) [7,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Copper is one of the agents involved in the oxidative stress [2,24] by the formation of ROS [25,26]; the exposure of marine mollusks to this metal induces lipid peroxidation [27]. Against these hazards, mussels, particularly the species Perna perna and Mytilus galloprovincialis, have developed enzymatic antioxidant defense mechanisms such as super oxide dismutase (SOD, EC 1.15.1.1) or CAT (EC 1.11.1.6) [7,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that both metals caused high levels of hemocyte apoptosis, necrosis and mortality after a 24 h in vitro incubation at certain concentrations ranging from 10-1000 µmol L (phenoloxidase, reactive oxygen species generation, cyclooxygenase, COX, activity, cell viability, cell-adherence to polystyrene microwells, phagocytosis) of the species. In a similar work by Gagnaire et al [57], by exposing haemocytes collected from Crassostrea gigas, they found no significant influence on the haemocyte of cadmium concentrations ranging from 3 × 10 -11 M to 3 × 10 -4 M but on exposure to 2 × 10 -4 M of mercury, mass mortality (80%) was recorded at 4-24 h assay. Choi et al [59] documented the effects of cadmium doses and duration on the heat shock protein 90 (HSP90) messenger RNA, mRNA, glutamate pyruvate transaminase, GPT, and glutamate oxaloacetate transaminase, GOT, in the gills, digestive glands and haemolymph of pacific oysters, Crassostrea gigas.…”
Section: Biochemical Biomarkers Immunotoxic/genotoxic Biomarkersmentioning
confidence: 79%
“…They observed that at high concentrations (10 -6 -10 -4 M) of mercuric chloride, silver nitrate, Zinc and Cadmium exposures, could result in reduced or impaired haemocyte phagocytic activity and cell viability. Gagnaire et al and Sokolova et al [57,58] investigated the adverse effects of cadmium, Cd and mercury, Hg, exposures on the defence mechanisms of Pacific oysters, Crassostrea gigas. They reported that both metals caused high levels of hemocyte apoptosis, necrosis and mortality after a 24 h in vitro incubation at certain concentrations ranging from 10-1000 µmol L (phenoloxidase, reactive oxygen species generation, cyclooxygenase, COX, activity, cell viability, cell-adherence to polystyrene microwells, phagocytosis) of the species.…”
Section: Biochemical Biomarkers Immunotoxic/genotoxic Biomarkersmentioning
confidence: 99%
“…A concentração de metal observada em uma amostra de hemolinfa pode apresentar correlação significativa e positiva com a da brânquia e a do hepatopâncreas, porém em valores 10 a 20 vezes inferiores (Cherkasov et al, 2007). O aumento no número total de hemócitos, bem como a mudança nas proporções dos tipos celulares (granulócitos e hialinos), já foi relacionado com o efeito à exposição por metal em bivalves (Pipe et al, 1999;Gagnairea et al, 2004).…”
Section: Cinética De Metais Nos Moluscos Bivalvesunclassified